2019
DOI: 10.7759/cureus.4743
|View full text |Cite
|
Sign up to set email alerts
|

Growing Old Too Fast: A Rare Case of Werner Syndrome

Abstract: Werner syndrome (WS) is rare adult-onset progeria characterized by premature aging and early death. Patients develop normally until adolescence and usually present in early adulthood. Our case highlights a common presentation of this uncommon disease, wherein a 29-year-old non-obese male with no known risk factors developed uncontrolled diabetes, hypertriglyceridemia, and rapidly progressive atherosclerotic vascular disease. Careful observation with attention to the presence of characteristic physical features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Hypertriglyceridemia should also be noted. It was reported that a 29-year-old patient with Werner syndrome and hypertriglyceridemia (triglyceride level of 3900 mg/dL) had advanced three-vessel disease requiring coronary artery bypass graft surgery [ 45 ]. Therefore, in addition to statins, management of hypertriglyceridemia may also be needed.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertriglyceridemia should also be noted. It was reported that a 29-year-old patient with Werner syndrome and hypertriglyceridemia (triglyceride level of 3900 mg/dL) had advanced three-vessel disease requiring coronary artery bypass graft surgery [ 45 ]. Therefore, in addition to statins, management of hypertriglyceridemia may also be needed.…”
Section: Discussionmentioning
confidence: 99%
“…The average life expectancy in patients with WS is around 54 years [13]. The cause of death in these patients is a myocardial infarction, or malignant…”
Section: Case Discussionmentioning
confidence: 99%
“…The causative gene is WRN on the short arm of chromosome 8. About 70% of the cases reported to date are Japanese, and 1 in 150 Advance Publication Journal of Atherosclerosis and Thrombosis Accepted for publication: August 16, 2021 Published online: September 11, 2021 disease requiring coronary artery bypass surgery 78) . In addition to statins to hypercholesterolemia, adequate management of hypertriglyceridemia may also be required.…”
Section: Werner Syndromementioning
confidence: 99%